The health implications of low hemoglobin deferral in infrequent blood donors - Annen, Kyle (Transfusion, 2014)
BACKGROUND: The causes of anemia in infrequent blood donors deferred for low hemoglobin (Hb) are not well known. We sought to assess this via surveys of infrequent, nonmenstruating deferred blood donors at two institutions, BloodCenter of Wisconsin and Puget Sound Blood Center. STUDY DESIGN AND METHODS: Men at least 18 years of age and women at least 50 years of age who were deferred for low Hb (≤12.5 g/dL), had not more than one donation in the year prior to deferral, and did not successfully donate in the 3 months after their deferral were surveyed. RESULTS: The total response rate was 380 donors or 34% of those contacted. Of the respondents, 141 had sought medical advice about their low Hb. Of these, 90 were confirmed to have anemia and 13 reported serious disease requiring medical intervention, including mantle cell lymphoma, multiple myeloma, and gastrointestinal bleeding. CONCLUSIONS: A small but concerning number of infrequent blood donors deferred for low Hb have an underlying illness that is severe and would benefit from medical attention. Donors deferred for low Hb who have a high risk for serious underlying illness should be provided targeted educational information advising them to seek additional medical care.